PENGARUH GENDER TERHADAP PERBEDAAN SPESTFIC VALUES PADA MAHASISWA AKUNTANSI - Purnamasari, Dian Indri (Fakultas Bisnis UKDW, 2007)
Ihe problans concerning to the ethics in auditing profession is closely related to ihe values of the individuals involving in the profession. The study aims at finding empirical eyidences whiher *eie * the differau in tlrc specific vahrcs of the female and male students of accounting. Lhe results of the analysis of independent sample t-test indicate that there is the difference in specific values between the female and nale sAdq* of accumting. In other words, the gender gives impact tothe difiaance in the specific values of the male students of accounting. hrths ualysis hdicates ttut in fact the difference in the specific values is cansed by tlre presenge of the impact of gender on the aesthetic values, while fudividual, social and theoretical values between the fe- ,nale md male studqrts of accounting are the same or do not have any inryt ot the individual, social anitheoretical values.Keyryods : Yalues, Gender, Stadenrts of Accounting, Auditing.